Kajian Keselamatan Paparan Radiasi Penggunaan Dental Sinar-X di Rumah Sakit Akademis Kota Makassar - Muh Rusli (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: This study was designed to evaluate radiation-safety conditions related to exposure from dental X-ray procedures at the Radiology Unit of Akademis Hospital Makassar. In routine clinical practice, variations in distance, exposure time, and positioning can influence the amount of scattered radiation received by surrounding areas. Given the importance of maintaining exposure levels within recommended safety limits, an assessment of dose accuracy at different measurement points was carried out. Methods: Radiation measurements were conducted at a fixed tube potential of 70 kV and a tube current of 9 mA. Dose readings were taken at four distances (1 m, 2 m, 3 m, and 4 m) and under four exposure-time settings (0.15 s, 0.19 s, 0.23 s, and 0.27 s). Measurements were also performed from four directions relative to the X-ray source—front, left, right, and rear. All data were recorded using standardized dosimetric procedures to determine which combination yielded optimal dose accuracy. Results: The analysis showed that the most favorable dose accuracy was obtained at a distance of 3 meters with an exposure time of 0.19 seconds, measured from the posterior direction. Under these conditions, the recorded dose was 0.87 µSv/h, representing the most stable and reliable value among all tested variations. Conclusions: The findings indicate that maintaining a distance of at least 3 meters, combined with appropriate exposure-time selection, can significantly enhance dose accuracy and improve radiation-safety conditions in dental X-ray environments. These results highlight the importance of optimizing positioning and exposure parameters to support safer radiographic practice. Keywords: Dental X-ray; radiation safety, dose accuracy, exposure parameters, scattered radiation; dosimetry; distance variation